Crystal structure and magnetoelectric properties of CrFeO3-doped BaZr0.1Ti0.9O3 multiferroic ceramics. (October 2022) - Klinbumrung, A.; Kidkhunthod, P.; Jantaratana, P.; Yimnirun, R.; Prasatkhetragarn, A.
Abstract: Chromium ferrite-doped barium zirconate titanate multiferroic materials in (1-x)BaZr0.1 Ti0.9 O3 – (x)CrFeO3 ; BZT-CF) system, when x = 0, 2, 4, 6, 8 and 10 mol%, were prepared by the solid-state reaction technique. Phase formation, lattice parameter, and electronic state of materials were characterized by x-ray diffraction (XRD) and x-ray absorption near-edge spectroscopy (XANES) techniques. It was found that the undoped BZT ceramic showed a single tetragonal phase without the secondary phase. However, CF-doped BZT ceramic at 2–10 mol% reveals that the tetragonal phase was changed to the orthorhombic phase. Lattice parameter and dislocation density have increased with increasing CrFeO3 content, representing the crystal structure's imperfection in interesting material. The magnetic and magnetoelectric of materials were characterized by the vibrating sample magnetometer (VSM) technique. It was found that all-ceramic exhibits a paramagnetic behavior. However, all doped ceramics showed a magnetic field response value better than undoped, with a maximum magnetodielectric coefficient (ME) of 18.3 × 10 −3  at 2 mol% of CF-doped. Highlight: The crystal structure of CrFeO3 -doped BaZr0.1 Ti0.9 O3 ceramics was deeply studied. XANES was used to explain the crystal structure of CF-doped BZT ceramics. A maximum paramagnetic value was observed at 2 mol% of CF.